Peran Moderasi Guru Pendidikan Agama Islam Dalam Membentuk Karakter dan Moral Peserta Didik - Sitompul, Julkhaidir; Suryadi, Fathur Rahman; Putri, Silva Vadila; Gusmaneli, Gusmaneli (IDRIS Darulfunun Institute, 2023)
This study aims to explore the role of moderation of Islamic religious education teachers in the formation of character and morals of students through Islamic religious education. Which is not only limited to the individual aspect, but also has broader social implications. This study uses literature research methods to determine the mediating role of Islamic religious education teachers in the formation of student character and morals. This study examines concepts and theories related to the role of teachers as conveyors of religious and moral values in Islamic education by analyzing relevant literature. The results of the literature review show that teachers play a central role in transmitting religious and moral values to students through certain teaching strategies. Therefore, this study provides a deeper understanding of the role of Islamic religious education teachers in shaping the character and morals of students, based on empirical and theoretical evidence in literature, especially in the context of Islamic religious education. The implications of these findings may provide a basis for developing more effective educational policies and practices to promote strong character and good morale in students. So this research will provide a clear understanding of how the role of Islamic religious education teachers, teacher-student interaction, curriculum, and holistic approaches can play a role in shaping the character of students. Recognizing and appreciating the important role of Islamic religious education teachers can be an important step in producing a generation that is intelligent, with integrity, and able to live a life in accordance with the teachings of Islam.